Peer e-assessment and feedback for student selfregulation and strategic learning at university: Student perception - B. Gallego Noche; V. Quesada Serra; M.A. Gómez Ruiz; J. Cubero Ibáñez (Universitat Politècnica de València, 2017)
The implementation of successful assessment for learning practices requires a co-responsibility of students and teachers. Participative assessment practices and feedback are key elements in assessment for learning to enhance student's self-regulation and strategic learning. More specifically, through peer-assessment students participate in a dialogic process where they assess their co-equals' performances and tasks offering constructive feedback. In such cases, technologies can facilitate and enrich the whole process. This paper provides an insight of student perceptions about their participation in peer-assessment and peer-feedback practices using information and communication technologies (ICT). Nine lecturers from different studies and 195 students participated in the research. Data gathering was implemented with a questionnaire that questioned about the possibilities and difficulties of three main topics: peer-assessment and peer-feedback process, the assessment task and the use of technologies to support the process. Results show positive appraisal of students in all the categories. Participants seem to highlight that providing peer-assessment and feedback enhance their critical skills when assessing their own performance. Still, to improve the results there is a need to train students in assessment, communication and technologies. To conclude, some prospective research actions are drawn stressing the contributions to feedback that electronic and virtual resources can provide.